(untitled) (Research, Society and Development, 2021)
Introduction: There is a growing demand for aesthetic restorations that naturally reproduce the characteristics of the dental structure. For this, it is necessary that the dentist understands the mimicry of natural teeth, especially their color, to obtain satisfactory aesthetic restorations. Objectives: Thus, the objective was to discuss about the steps and the clinical procedure for a correct selection of tooth color, in order to obtain excellence in restorations and provide the academic community with in-depth content on the subject. Materials and Methods: A bibliographic search was carried out on the following online research bases: PUBMED / MEDLINE, LILACS, BBO, Scielo, Google Scholar, through the screening of relevant articles published between 2000 and 2020. The following descriptors were used for the search: Composite Resins, Compomers, Color Selection, Tooth (Tooth). Results: The studies obtained with the research demonstrate that the chromatic selection of the tooth is complex and should be done with a theoretical and practical basis. In the field of cosmetic dentistry, color is divided into three dimensions: hue, chroma and value. Properties that directly influence color observation and selection. In addition, the restoration must reproduce the translucent enamel and opalescent characteristics of dentin. Conclusion: Color selection is one of the most important steps in anterior tooth restorations. Therefore, clinical experience and study on the choice of teeth color is essential, as well as a constant updating of the subject, in order to obtain subtle and imperceptible restorations.